HYDROGEOLOGY. THE ORENBURG FRACTURE ZONE AND ITS FLUID POTENTIAL - Kortsenshteyn V.N. (My University, 1988)
In November 1966, geologists discovered a large anticlinal fold in the vicinity of the Sol'-Iletskiy swell which overlaps the northern flank of the Caspian Basin. This tectonic feature subsequently became widely known, when the Orenburg gas condensate field was discovered in its Artinskian Middle Carboniferous part of the section. Using this field as an example, the author discusses the properties of gas-liquid (fluidal) low-temperature fields that yield commercial flows of hydrocarbon gases and acidic gases (CnH2n+2, H2S, CO2), sporadic flows of oil from a rim of patchy structure, and high-pressure chloride and sodium-chloride brines. Careful analysis of data obtained during the long period of operation of the field indicates that the process of discharge of fluids of this composition has much in common with the mechanism of infiltration metasomatism, in which fluids are injected into an original pore-and-fissure space of complex structure in calcareous reservoirs, subsequently producing a kind of 'print' that is detectable by both direct and indirect methods.
Keywords: Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная